PROPAGANDA: A STRATEGY TO SPREAD THE IDEOLOGY IN PAKISTAN IN THE NOVEL I AM MALALA BY MALALA YOUSAFZAI AND CHRISTINA LAMB (2013) - Kartika, Ruly; Rahmi, Sri Warsidah (Elite : English and Literature Journal, 2017)
Abstract This study examines the analysis of propaganda in the literature as revealed in the novel I Am Malala. The purpose of this research is to analyze and depict Taliban's Taliban propaganda as a strategy to gain power in Pakistan. Their strongest effort is to spread propaganda throughout the community to the region. The propaganda theory, Jacques Ellul, is used to find out how the Taliban use propaganda as their strategy and to know the qualitative methods related to the description and explanation of the phenomenon of propaganda. Through this research, the author discovers the type of propaganda created by the author to clarify the conflict that has occurred between the Taliban and the community. Then, the author gives the propaganda purpose. This study implies how propaganda has become a social phenomenon of life and implicitly forms a perspective in viewing around the community. Abstract Penelitian ini mempelajari tentang analisis propaganda dalam literatur seperti yang terungkap dalam novel I Am Malala. Tujuan dari penelitian ini adalah untuk menganalisis dan menggambarkan propaganda Taliban yang dilakukan Taliban sebagai strategi untuk mendapatkan kekuasaan di Pakistan. Upaya terkuat yang mereka lakukan adalah menyebarkan propaganda ke seluruh masyarakat ke daerah. Teori propaganda, Jacques Ellul, digunakan untuk mengetahui cara Taliban menggunakan propaganda sebagai strategi mereka dan untuk mengetahui metode kualitatif yang berkaitan dengan deskripsi dan penjelasan fenomena propaganda. Melalui penelitian ini, penulis menemukan jenis propaganda yang diciptakan oleh penulis untuk mengklarifikasi konflik yang telah terjadi antara Taliban dan masyarakat. Kemudian, penulis memberikan tujuan propaganda itu. Penelitian ini berimplikasi bagaimana propaganda telah menjadi fenomena sosial kehidupan dan secara implisit membentuk perspektif dalam melihat sekitar masyarakat.